STRUKTUR MODAL, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN - Ni Luh Gede Sri Fajaryani; Elly Suryani (JRAK, 2018)
This study aims to examine the effect of capital structure as measured by the debt to equity ratio (DER), liquidity measured by the current ratio (CR), and firm size measured by the natural logarithm (Ln) of total assets against financial performance as measured by return on equity (ROE) in companies in the property and real estate sub-sector from 2013-2016. The method of determining the sample used was purposive sampling. The sample used was 40 companies. The data analysis technique used is panel data regression analysis consisting of chow test, hausman test, and lagrange multiplier test using Eviews 9.0 software. The results showed that the capital structure (DER), liquidity (CR), and company size simultaneously had a significant effect on financial performance (ROE). Partially the capital structure (DER) and liquidity (CR) had a significant negative effect on financial performance (ROE). Whereas company size (Ln Total Assets) did not have a significant effect on financial performance (ROE).